TINGKAT KEUNTUNGAN DAN USIA PERUSAHAAN TERHADAP LEVERAGE: ESTIMASI MODEL DATA PANEL DI INDONESIA - Rizka Hadya; Joni Fernandes (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2020)
This research have been found that profitability and firm age affect leverage. The selected objects is all companies which are listed in Indonesia Stock Exchange during period 2013-2017. We select the samples use the data panel regression model. There are 96 companies have been selected as samples whit technique purposive sampling. The result by partial test profitability and firm age, has a negative significant influence to the leverage, shows that the r-square value of 91,76% which means the profitability and age of the company have the ability to explain leverage of 91,76% and while remaining 8,24% is explained by other variables which are not studied. This is relevant to the capital structure theory. Capital structure is something that is very important for the company which involves funding that carries out the company's operations so that it produces profits. Another factor is the firm age, a long-standing and reputable company will be able to overcome creditworthiness issues when it decides to use debt funding sources.